Can smart city construction be the answer to sustainable development? Evidence from Chinese corporates - Peng, Weihui; Li, Jie; Ren, Xiang (Frontiers in Environmental Science, 2024)
The construction of smart cities plays a pivotal role in promoting regional sustainability by utilizing technology-driven urban development in the digital era. This study employs the difference-in-differences model to empirically analyze the impact of the smart city pilot policy on corporate carbon intensity, using data from Chinese A-share listed corporates from 2009 to 2021. The findings are as follows: First, the smart city pilot policy significantly reduces corporate carbon intensity in pilot cities, and this conclusion remains robust after a series of sensitivity tests. Second, the policy exhibits heterogeneous effects on corporate carbon intensity across different industries and city locations, with more pronounced effects observed in central cities, traditional industries, and heavily polluting industries. Third, mechanism analysis reveals that the policy reduces corporate carbon intensity through three channels: promoting technological innovation, increasing external market attention, and providing ex-ante government subsidies.